An innovative case management intervention for people at high risk of permanent work disability to improve rehabilitation coverage and coordination of health services: a randomized controlled trial (AktiFAME, DRKS00024648) - Lea Remus; Marei Grope; Stella Lemke; Matthias Bethge (BMC, 2022)
Abstract Background German social law offers services from various providers and agencies for people with chronic disease or disability. Claiming services requires a high level of information and communication. Dealing with a multitude of actors, such as pension insurance agencies, job centers, employers, physicians, and psychotherapists, and coordinating between and with these actors can delay or prevent the utilization of necessary measures like medical or vocational rehabilitation. We developed a case management intervention for people at high risk of receiving a disability pension to address these challenges. Methods/design Our randomized controlled trial tests the effectiveness of the multi-component AktiFAME strategy (Active access, counseling, and case management for people at high risk of permanent work disability). This strategy is comprised of four modules: screening and postal contact, telephone counseling, an initial one-on-one interview, and case management. The randomized controlled trial is complemented by an observational study that exclusively involves the individuals participating in case management and accompanies the implementation of the case management intervention. We enroll 9000 individuals aged 18 to 65 years who were identified as being at increased risk for receiving a disability pension based on administrative data from the German Pension Insurance North but who have not yet applied for rehabilitation. Half of the individuals are randomly assigned to the intervention group and the other half to the control group. The intervention group is contacted and informed about a case management intervention, whereas the control group is not. The primary outcome of the randomized controlled trial is the utilization of rehabilitation services from the German Pension Insurance North (medical or vocational rehabilitation). Data on rehabilitation will be provided by the German Pension Insurance North 1 year after random allocation. Secondary and tertiary outcomes cover additional administrative data (e.g., employment and welfare benefits) and a range of patient-reported outcome measures. Discussion This randomized controlled trial is designed to determine the effectiveness of a newly implemented multi-component strategy to promote participation and rehabilitation coverage among individuals at high risk of receiving a disability pension. Trial registration German Clinical Trials Register (DRKS00024648, April 27, 2021).